Lebanon : Report on Interim Staff Visit. (IMF Staff Country Reports; Country Report, 2004)
This Report on the Interim IMF Staff Visit to Lebanon provides information on economic and policy developments since the Article IV discussions of February-March 2004. It updates the IMF staff's projections, medium-term framework, and related Debt Sustainability Analysis. All available indicators point to a significant acceleration in growth, which is projected to reach 5 percent in 2004. Strong export and tourism receipts and a recovery in construction activity are the driving factors behind the strengthening recovery. A modest acceleration of inflation to about 3 percent is expected in 2004.